Preparation method of bacteriostatic formaldehyde-removing regenerated cellulose fiber

Through the treatment and copolymerization and cross-linking technology of titanate coupling agent, the dispersion of carbon quantum dots and TiO2 in cellulose spinning liquid is solved, the mechanical properties and antibacterial effects of the fiber are improved, and the efficient formaldehyde removal and Antibacterial effect.

CN119194639APending Publication Date: 2024-12-27DEZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411223838.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In viscose spinning liquid, uneven dispersion of carbon quantum dots and TiO2 leads to clogging of spinneret holes and degradation of fiber mechanical properties, making it difficult to achieve efficient purification of antibacterial and formaldehyde removal.

Method used

After treatment with titanate coupling agent, the carbon quantum dots were uniformly attached to the surface of TiO2 and modified with γ-methacryloyloxypropyltrimethoxysilane. Then, copolymerized crosslinking was used to generate crosslinked polyvinylpyrrolidone packages. Carbon-covered quantum dots/TiO2 particles improve their dispersion and compatibility with cellulose macromolecules.

Benefits of technology

The uniform dispersion of carbon quantum dots/TiO2 in cellulose spinning liquid was achieved, which improved the mechanical properties and antibacterial effect of the fibers. The formaldehyde removal rate was greater than 90% under visible light irradiation, and the 98% inhibition was maintained after 50 washes. Bacteria rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194639A_ABST
    Figure CN119194639A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fiber textile, and particularly relates to a preparation method of an antibacterial formaldehyde-removing regenerated cellulose fiber, which comprises the following steps: preparation of carbon quantum dot / TiO2 particles, modification, copolymerization crosslinking, preparation of a composite carbon quantum dot / TiO2 photocatalyst dispersion liquid, preparation of a blended spinning solution, and spinning molding. The preparation method comprises the following steps: firstly, treating TiO2 by using a titanate coupling agent, so that carbon quantum dots can be uniformly and stably attached to the surface of the TiO2 treated by the coupling agent to obtain carbon quantum dot / TiO2 particles, and then modifying unsaturated double bonds on the surfaces of the particles by using gamma-methacryloxypropyltrimethoxysilane; finally, cross-linked polyvinylpyrrolidone is generated on the surfaces of the particles in a copolymerization cross-linking mode for coating, and the purpose of improving the dispersity of the carbon quantum dot / TiO2 particles is achieved. The dry breaking strength of the prepared bacteriostatic formaldehyde-removing regenerated cellulose fiber is 2.55-2.7 cN / dtex, the wet breaking strength is 1.42-1.58 cN / dtex, and the formaldehyde removal rate is greater than 90% after the regenerated cellulose fiber is irradiated by visible light for 3 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fiber textiles, and in particular relates to a method for preparing bacteriostatic and formaldehyde-removing regenerated cellulose fiber. Background Art

[0002] As a new type of luminescent material, carbon quantum dots have the advantages of excellent optical properties, good water solubility, low toxicity, environmental friendliness, wide source of raw materials, low cost, and good biocompatibility. They have attracted much attention due to their simple preparation strategy, excellent fluorescence performance, and non-toxicity. Carbon quantum dots have broad application prospects in many fields such as medical imaging technology, biosensors, metal ion detection, environmental monitoring, chemical analysis, catalyst preparation, and energy development. Titanium dioxide, as a representative photocatalyst material, can produce strong oxidizing substances under ultraviolet light, which can effectively degrade toxic and harmful gases in the air such as formaldehyde, and efficiently purify the air; at the same time, it can effectively kill a variety of bacteria.

[0003] Patent CN106902803A discloses a composite photocatalytic system CQDS-KNbO with strong redox activity 3 , which can degrade organic pollutants under visible light irradiation and produce hydrogen at the same time; Patent CN110404524A discloses a method for preparing a carbon quantum dot / titanium dioxide composite photocatalyst and introduces its application in degrading organic dyes; Patent CN105879856A discloses a method for preparing a carbon quantum dot / bismuth molybdate nanosheet composite photocatalytic material, which is used to degrade toxic organic pollutants that are difficult to biodegrade, such as rhodamine B and methyl orange; Patent CN112626846A discloses that viscose fibers are treated with a carbon quantum dot solution without desorption. The sulfur treatment process obtains viscose fibers with less irritating odor and antibacterial and mosquito repellent properties; Patent CN102944538A discloses that polyacrylonitrile and fluorescent carbon quantum dots are used as raw materials, and electrospinning technology is used to prepare fluorescent carbon quantum dots / polyacrylonitrile composite nanofiber membranes, thereby obtaining nanofiber membrane materials loaded with fluorescent carbon quantum dots, which are used to prepare sensitive materials for highly sensitive thin-film sensors; Patent CN114108314A discloses that carboxymethyl-modified viscose fibers are treated with rich amine quantum dots to prepare carbon quantum dot-functionalized fluorescent viscose fibers. Patent CN115467158A discloses that Ag / AgBr / Fe is prepared by synthesizing photocatalysts through surface plasma action. 2 O 3 Functional fabric, the fabric has the function of removing formaldehyde when irradiated with 365nm ultraviolet lamp as the light source.

[0004] Utilizing the upconversion properties of carbon quantum dots to convert visible light into ultraviolet light to excite TiO 2 Generate electrons and holes to achieve TiO 2The material has photocatalytic activity in the near-infrared region, achieving the effects of antibacterial, formaldehyde removal, and efficient air purification. 2 If added directly, due to uneven dispersion, it is easy to agglomerate and cause blockage of the spinneret hole, and it will have a certain impact on the mechanical properties of the fiber. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a method for preparing antibacterial and formaldehyde-removing regenerated cellulose fiber, which can improve the 2 Dispersibility in viscose spinning solution is an object of the invention.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for preparing bacteriostatic and formaldehyde-removing regenerated cellulose fiber, the preparation method comprising the following steps:

[0008] S1, Carbon quantum dots / TiO 2 Particle preparation

[0009] Titanate coupling agent, TiO 2 Add to deionized water, stir and mix to obtain a mixed system; add the mixed system to a JFS-550 type dispersing sand mill for grinding and dispersion, add the carbon quantum dot solution to the mixed system after grinding, stir and mix for 30 to 60 minutes, so that the carbon quantum dots can be evenly and stably attached to the TiO treated with the coupling agent. 2 After centrifugation, washing, filtration and drying, carbon quantum dots / TiO 2 particle.

[0010] Preferably, the particle size of the carbon quantum dots is 20 to 50 nm, and the TiO 2 The particle size is 100~200nm.

[0011] Preferably, the grinding and dispersing time is 60 to 90 minutes, and the rotation speed is 1500 to 2000 r / min.

[0012] Preferably, the titanate coupling agent, TiO 2 The mass ratio of deionized water is 5-8:15-20:90-100.

[0013] Preferably, the concentration of the carbon quantum dot solution is 10-20wt%; the carbon quantum dots in the carbon quantum dot solution are TiO 2 1-2% of mass.

[0014] Preferably, the drying temperature is 40-50° C. and the drying time is 24-36 hours.

[0015] S2. Modification

[0016] Carbon quantum dots / TiO 2 The particles were added to anhydrous ethanol, and then γ-methacryloxypropyltrimethoxysilane was added. After stirring for 20 to 30 minutes, the pH was adjusted to 4.5 to 6, and the temperature was raised to 40 to 50 ° C for 90 to 120 minutes. 2 The particle surface is modified with unsaturated double bonds. After the reaction, the modified carbon quantum dots / TiO are obtained by centrifugation, washing, filtration and drying. 2 particle.

[0017] Preferably, the carbon quantum dots / TiO 2 The mass ratio of the particles to anhydrous ethanol is 1:10-15.

[0018] Preferably, the amount of γ-methacryloxypropyltrimethoxysilane added is carbon quantum dots / TiO 2 18-22% of particle mass

[0019] Preferably, the drying temperature is 40-50° C. and the drying time is 24-36 hours.

[0020] S3, copolymerization and cross-linking

[0021] Modified carbon quantum dots / TiO 2 The particles were added to anhydrous ethanol and stirred for 20 to 30 minutes, and then N-vinyl pyrrolidone, initiator, and cross-linking agent were added and stirred for 10 to 20 minutes. The temperature was raised to 60 to 70 °C and the copolymerization and cross-linking reaction was performed for 4 to 6 hours. 2 The surface of the particles is cross-linked with polyvinyl pyrrolidone to modify the carbon quantum dots / TiO 2 The particles are coated, and after the reaction, they are centrifuged, washed, filtered, and dried to obtain composite carbon quantum dots / TiO 2 Photocatalyst.

[0022] Preferably, the modified carbon quantum dots / TiO 2 The mass ratio of the particles to anhydrous ethanol is 1:10-15.

[0023] Preferably, the amount of N-vinyl pyrrolidone added is 2 32-40% of the particle mass.

[0024] Preferably, the added amount of the initiator is 0.5-1.5% of the mass of N-vinyl pyrrolidone, and the added amount of the cross-linking agent is 2-4% of the mass of N-vinyl pyrrolidone.

[0025] Furthermore, the initiator is azobisisobutyronitrile, and the crosslinking agent is N,N, -Methylenebisacrylamide.

[0026] Preferably, the drying temperature is 50-60° C. and the drying time is 12-24 hours.

[0027] S4, composite carbon quantum dots / TiO 2 Preparation of photocatalyst dispersion

[0028] Composite carbon quantum dots / TiO 2 The photocatalyst was added into deionized water and stirred for 10-20 min to obtain composite carbon quantum dots / TiO 2 Photocatalyst dispersion.

[0029] Preferably, the composite carbon quantum dots / TiO 2 The mass ratio of the photocatalyst to deionized water is 1:8-10.

[0030] S5. Preparation of blended spinning solution

[0031] Cellulose pulp is used as raw material, and cellulose spinning solution is prepared through the processes of impregnation, pressing, crushing, aging, yellowing, dissolving, filtering, degassing, etc. 2 The photocatalyst dispersion is added in proportion during the dissolution process or injected before spinning and mixed evenly to form a blended spinning solution.

[0032] Preferably, the viscosity of the cellulose spinning solution is 35 to 55 s (falling ball method), and the maturity is 13 to 17 mL (10% NH 4 CL), the methyl fiber content is 8.6~9.2wt%.

[0033] Preferably, the composite carbon quantum dots / TiO 2 Composite carbon quantum dots / TiO in photocatalyst dispersion 2 The photocatalyst is 0.2-1.0wt% of the methyl cellulose content in the cellulose spinning solution.

[0034] S6, Spinning

[0035] The blended spinning solution is sprayed out from the spinneret and then formed into a primary fiber bundle through a coagulation bath. After inter-disk drawing, two-bath drawing, post-treatment and other processes, the antibacterial and formaldehyde-removing regenerated cellulose fiber prepared by the invention is obtained.

[0036] Preferably, in the coagulation bath, sulfuric acid is 100-150 g / L, zinc sulfate is 30-50 g / L, sodium sulfate is 210-240 g / L, and the reaction temperature is 40-45°C.

[0037] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are:

[0038] 1. The antibacterial and formaldehyde-removing regenerated cellulose fiber prepared by the present invention has excellent mechanical properties, wherein the dry breaking strength is 2.55-2.7 cN / dtex and the wet breaking strength is 1.42-1.58 cN / dtex.

[0039] 2. The antibacterial and formaldehyde-removing regenerated cellulose fiber prepared by the present invention has good antibacterial effect. After washing 50 times with water, the antibacterial rate against Staphylococcus aureus is greater than 98%, the antibacterial rate against Escherichia coli is greater than 96%, and the antibacterial rate against Candida albicans is greater than 97% (determined in accordance with "GB / T 20944.3-2008 Evaluation of Antibacterial Properties of Textiles").

[0040] 3. The antibacterial and formaldehyde-removing regenerated cellulose fiber prepared by the present invention has a formaldehyde removal effect under visible light, and the formaldehyde removal rate is greater than 90% under visible light irradiation for 3 hours (determined in accordance with "FZ T 01167-2022 Textile Formaldehyde Removal Efficiency Test Method Photocatalytic Method").

[0041] 4. The present invention firstly treats TiO 2 Titanate coupling agent treatment is used to make carbon quantum dots evenly and stably adhere to the TiO 2 Surface, get carbon quantum dots / TiO 2 Particles; Using γ-methacryloxypropyltrimethoxysilane on carbon quantum dots / TiO 2 The particle surface is modified with unsaturated double bonds to obtain modified carbon quantum dots / TiO 2 particles; finally, the modified carbon quantum dots / TiO 2 The surface of the particles is cross-linked with polyvinyl pyrrolidone to modify the carbon quantum dots / TiO 2 The particles are coated to increase the carbon quantum dots / TiO 2 The purpose is to improve the dispersibility of particles and compatibility with cellulose macromolecules.

[0042] 5. Composite carbon quantum dots / TiO 2 The cross-linked polyvinyl pyrrolidone on the surface of the photocatalyst contains N-heterocycles and carbonyl groups. Under the acidic conditions of the coagulation bath, the cross-linked polyvinyl pyrrolidone is protonated to form hydrogen bonds with the hydroxyl groups on the cellulose macromolecules, further improving the strength of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a formaldehyde removal trend diagram of an embodiment of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with specific embodiments.

[0045] Example 1

[0046] S1, Carbon quantum dots / TiO 2 Particle preparation

[0047] Titanate coupling agent, TiO 2 Add to deionized water, stir and mix to obtain a mixed system; add the mixed system to a JFS-550 type dispersing sand mill for grinding and dispersion, add the carbon quantum dot solution to the mixed system after grinding, stir and mix for 50 minutes, so that the carbon quantum dots can be evenly and stably attached to the TiO treated with the coupling agent. 2 After centrifugation, washing, filtration and drying, carbon quantum dots / TiO 2 particle.

[0048] The particle size of the carbon quantum dots is 30 nm, and the TiO 2 The particle size is 150nm.

[0049] The grinding and dispersing time is 80 minutes and the rotation speed is 1600 r / min.

[0050] The titanate coupling agent, TiO 2 The mass ratio of sodium iodide and deionized water is 7:17:95.

[0051] The concentration of the carbon quantum dot solution is 15wt%; the carbon quantum dots in the carbon quantum dot solution are TiO 2 1.6% of mass.

[0052] The drying temperature is 45° C. and the drying time is 30 h.

[0053] S2. Modification

[0054] Carbon quantum dots / TiO 2 The particles were added to anhydrous ethanol, and then γ-methacryloxypropyltrimethoxysilane was added. After stirring for 25 minutes, the pH was adjusted to 5, and the temperature was raised to 45°C for 100 minutes. 2 The particle surface is modified with unsaturated double bonds. After the reaction, the modified carbon quantum dots / TiO are obtained by centrifugation, washing, filtration and drying. 2 particle.

[0055] The carbon quantum dots / TiO 2 The mass ratio of particles to anhydrous ethanol is 1:12.

[0056] The amount of γ-methacryloxypropyltrimethoxysilane added is carbon quantum dots / TiO 2 20% of particle mass

[0057] The drying temperature is 45° C. and the drying time is 30 h.

[0058] S3, copolymerization and cross-linking

[0059] Modified carbon quantum dots / TiO 2 The particles were added to anhydrous ethanol and stirred for 25 min, then N-vinyl pyrrolidone, initiator, and cross-linking agent were added and stirred for 15 min. The temperature was raised to 65 °C and the copolymerization and cross-linking reaction was carried out for 5 h. 2 The surface of the particles is cross-linked with polyvinyl pyrrolidone to modify the carbon quantum dots / TiO 2 The particles are coated, and after the reaction, they are centrifuged, washed, filtered, and dried to obtain composite carbon quantum dots / TiO 2 Photocatalyst.

[0060] The modified carbon quantum dots / TiO 2 The mass ratio of particles to anhydrous ethanol is 1:12.

[0061] The amount of N-vinyl pyrrolidone added is the modified carbon quantum dots / TiO 2 36% of the particle mass.

[0062] The added amount of the initiator is 1% of the mass of N-vinyl pyrrolidone, and the added amount of the crosslinking agent is 3% of the mass of N-vinyl pyrrolidone.

[0063] The initiator is azobisisobutyronitrile, and the crosslinking agent is N,N , -Methylenebisacrylamide.

[0064] The drying temperature is 55° C. and the drying time is 18 hours.

[0065] S4, composite carbon quantum dots / TiO 2 Preparation of photocatalyst dispersion

[0066] Composite carbon quantum dots / TiO 2 The photocatalyst was added into deionized water and stirred for 15 min to obtain composite carbon quantum dots / TiO 2 Photocatalyst dispersion.

[0067] The composite carbon quantum dots / TiO 2 The mass ratio of photocatalyst to deionized water was 1:9.

[0068] S5. Preparation of blended spinning solution

[0069] Cellulose pulp is used as raw material, and cellulose spinning solution is prepared through the processes of impregnation, pressing, crushing, aging, yellowing, dissolving, filtering, degassing, etc. 2 The photocatalyst dispersion is added into the cellulose spinning solution in proportion by injection before spinning and mixed evenly to prepare a blended spinning solution.

[0070] The viscosity of the cellulose spinning solution is 40s (falling ball method), and the maturity is 15mL (10% NH 4 CL), the methyl fiber content is 9wt%.

[0071] The composite carbon quantum dots / TiO 2 Composite carbon quantum dots / TiO in photocatalyst dispersion 2 The photocatalyst is 0.7wt% of the methyl cellulose content in the cellulose spinning solution.

[0072] S6, Spinning

[0073] The blended spinning solution is sprayed out from the spinneret and then formed into a primary fiber bundle through a coagulation bath. After inter-disk drawing, two-bath drawing, post-treatment and other processes, the antibacterial and formaldehyde-removing regenerated cellulose fiber prepared by the invention is obtained.

[0074] In the coagulation bath, sulfuric acid is 120 g / L, zinc sulfate is 40 g / L, sodium sulfate is 220 g / L, and the reaction temperature is 42°C.

[0075] Example 2

[0076] S1, Carbon quantum dots / TiO 2 Particle preparation

[0077] Titanate coupling agent, TiO 2 Add to deionized water, stir and mix to obtain a mixed system; add the mixed system to a JFS-550 type dispersing sand mill for grinding and dispersion, add the carbon quantum dot solution to the mixed system after grinding, stir and mix for 30 minutes, so that the carbon quantum dots can be evenly and stably attached to the TiO treated with the coupling agent. 2 After centrifugation, washing, filtration and drying, carbon quantum dots / TiO 2 particle.

[0078] The particle size of the carbon quantum dots is 20 nm, and the TiO 2 The particle size is 100nm.

[0079] The grinding and dispersing time is 60 minutes and the rotation speed is 1500 r / min.

[0080] The titanate coupling agent, TiO 2 The mass ratio of sodium iodide and deionized water is 5:15:90.

[0081] The concentration of the carbon quantum dot solution is 10wt%; the carbon quantum dots in the carbon quantum dot solution are TiO 2 1% of mass.

[0082] The drying temperature is 40° C. and the drying time is 36 hours.

[0083] S2. Modification

[0084] Carbon quantum dots / TiO 2 The particles were added to anhydrous ethanol, and then γ-methacryloxypropyltrimethoxysilane was added. After stirring for 20 minutes, the pH was adjusted to 4.5, and the temperature was raised to 40°C for 90 minutes. 2 The particle surface is modified with unsaturated double bonds. After the reaction, the modified carbon quantum dots / TiO are obtained by centrifugation, washing, filtration and drying. 2 particle.

[0085] The carbon quantum dots / TiO 2 The mass ratio of particles to anhydrous ethanol is 1:10.

[0086] The amount of γ-methacryloxypropyltrimethoxysilane added is carbon quantum dots / TiO 2 18% of particle mass

[0087] The drying temperature is 40° C. and the drying time is 36 hours.

[0088] S3, copolymerization and cross-linking

[0089] Modified carbon quantum dots / TiO 2 The particles were added to anhydrous ethanol and stirred for 20 min, then N-vinyl pyrrolidone, initiator, and crosslinker were added and stirred for 10 min. The temperature was raised to 60 °C and the copolymerization and crosslinking reaction was carried out for 6 h. 2 The surface of the particles is cross-linked with polyvinyl pyrrolidone to modify the carbon quantum dots / TiO 2 The particles are coated, and after the reaction, they are centrifuged, washed, filtered, and dried to obtain composite carbon quantum dots / TiO 2 Photocatalyst.

[0090] The modified carbon quantum dots / TiO 2 The mass ratio of particles to anhydrous ethanol is 1:10.

[0091] The amount of N-vinyl pyrrolidone added is the modified carbon quantum dots / TiO 2 32% of the particle mass.

[0092] The added amount of the initiator is 0.5% of the mass of N-vinyl pyrrolidone, and the added amount of the crosslinking agent is 2% of the mass of N-vinyl pyrrolidone.

[0093] The initiator is azobisisobutyronitrile, and the crosslinking agent is N,N , -Methylenebisacrylamide.

[0094] The drying temperature is 50° C. and the drying time is 24 hours.

[0095] S4, composite carbon quantum dots / TiO 2 Preparation of photocatalyst dispersion

[0096] Composite carbon quantum dots / TiO 2 The photocatalyst was added into deionized water and stirred for 10 min to obtain composite carbon quantum dots / TiO 2 Photocatalyst dispersion.

[0097] The composite carbon quantum dots / TiO 2 The mass ratio of photocatalyst to deionized water was 1:8.

[0098] S5. Preparation of blended spinning solution

[0099] Cellulose pulp is used as raw material, and cellulose spinning solution is prepared through the processes of impregnation, pressing, crushing, aging, yellowing, dissolving, filtering, degassing, etc. 2 The photocatalyst dispersion is added into the cellulose spinning solution in proportion by injection before spinning and mixed evenly to prepare a blended spinning solution.

[0100] The viscosity of the cellulose spinning solution is 35s (falling ball method), and the maturity is 13mL (10% NH 4 CL), the methyl fiber content is 8.6wt%.

[0101] The composite carbon quantum dots / TiO 2 Composite carbon quantum dots / TiO in photocatalyst dispersion 2 The photocatalyst is 0.2 wt% of the methyl cellulose content in the cellulose spinning solution.

[0102] S6, Spinning

[0103] The blended spinning solution is sprayed out from the spinneret and then formed into a primary fiber bundle through a coagulation bath. After inter-disk drawing, two-bath drawing, post-treatment and other processes, the antibacterial and formaldehyde-removing regenerated cellulose fiber prepared by the invention is obtained.

[0104] In the coagulation bath, sulfuric acid is 100 g / L, zinc sulfate is 50 g / L, sodium sulfate is 210 g / L, and the reaction temperature is 40°C.

[0105] Example 3

[0106] S1, Carbon quantum dots / TiO 2 Particle preparation

[0107] Titanate coupling agent, TiO 2Add to deionized water, stir and mix to obtain a mixed system; add the mixed system to a JFS-550 type dispersing sand mill for grinding and dispersion, add the carbon quantum dot solution to the mixed system after grinding, stir and mix for 60 minutes, so that the carbon quantum dots can be evenly and stably attached to the TiO treated with the coupling agent. 2 After centrifugation, washing, filtration and drying, carbon quantum dots / TiO 2 particle.

[0108] The particle size of the carbon quantum dots is 50 nm, and the TiO 2 The particle size is 200nm.

[0109] The grinding and dispersing time is 90 minutes and the rotation speed is 2000 r / min.

[0110] The titanate coupling agent, TiO 2 The mass ratio of sodium iodide and deionized water is 8:20:100.

[0111] The concentration of the carbon quantum dot solution is 20wt%; the carbon quantum dots in the carbon quantum dot solution are TiO 2 2% of mass.

[0112] The drying temperature is 50° C. and the drying time is 24 hours.

[0113] S2. Modification

[0114] Carbon quantum dots / TiO 2 The particles were added to anhydrous ethanol, and then γ-methacryloxypropyltrimethoxysilane was added. After stirring for 30 minutes, the pH was adjusted to 6, and the temperature was raised to 50°C for 120 minutes. 2 The particle surface is modified with unsaturated double bonds. After the reaction, the modified carbon quantum dots / TiO are obtained by centrifugation, washing, filtration and drying. 2 particle.

[0115] The carbon quantum dots / TiO 2 The mass ratio of particles to anhydrous ethanol is 1:15.

[0116] The amount of γ-methacryloxypropyltrimethoxysilane added is carbon quantum dots / TiO 2 22% of particle mass

[0117] The drying temperature is 50° C. and the drying time is 24 hours.

[0118] S3, copolymerization and cross-linking

[0119] Modified carbon quantum dots / TiO 2The particles were added to anhydrous ethanol and stirred for 30 min, then N-vinyl pyrrolidone, initiator, and crosslinking agent were added and stirred for 20 min. The temperature was raised to 70 °C and the copolymerization and crosslinking reaction was carried out for 6 h. 2 The surface of the particles is cross-linked with polyvinyl pyrrolidone to modify the carbon quantum dots / TiO 2 The particles are coated, and after the reaction, they are centrifuged, washed, filtered, and dried to obtain composite carbon quantum dots / TiO 2 Photocatalyst.

[0120] The modified carbon quantum dots / TiO 2 The mass ratio of particles to anhydrous ethanol is 1:15.

[0121] The amount of N-vinyl pyrrolidone added is the modified carbon quantum dots / TiO 2 40% of the particle mass.

[0122] The added amount of the initiator is 1.5% of the mass of N-vinyl pyrrolidone, and the added amount of the crosslinking agent is 4% of the mass of N-vinyl pyrrolidone.

[0123] The initiator is azobisisobutyronitrile, and the crosslinking agent is N,N , -Methylenebisacrylamide.

[0124] The drying temperature is 60° C. and the drying time is 12 hours.

[0125] S4, composite carbon quantum dots / TiO 2 Preparation of photocatalyst dispersion

[0126] Composite carbon quantum dots / TiO 2 The photocatalyst was added into deionized water and stirred for 20 min to obtain composite carbon quantum dots / TiO 2 Photocatalyst dispersion.

[0127] The composite carbon quantum dots / TiO 2 The mass ratio of photocatalyst to deionized water was 1:10.

[0128] S5. Preparation of blended spinning solution

[0129] Cellulose pulp is used as raw material, and cellulose spinning solution is prepared through the processes of impregnation, pressing, crushing, aging, yellowing, dissolving, filtering, degassing, etc. 2 The photocatalyst dispersion is added into the cellulose spinning solution in proportion by injection before spinning and mixed evenly to prepare a blended spinning solution.

[0130] The viscosity of the cellulose spinning solution is 55s (falling ball method), and the maturity is 17mL (10% NH4 CL), the methyl fiber content is 9.2wt%.

[0131] The composite carbon quantum dots / TiO 2 Composite carbon quantum dots / TiO in photocatalyst dispersion 2 The photocatalyst is 1.0wt% of the methyl cellulose content in the cellulose spinning solution.

[0132] S6, Spinning

[0133] The blended spinning solution is sprayed out from the spinneret and then formed into a primary fiber bundle through a coagulation bath. After inter-disk drawing, two-bath drawing, post-treatment and other processes, the antibacterial and formaldehyde-removing regenerated cellulose fiber prepared by the invention is obtained.

[0134] In the coagulation bath, sulfuric acid is 150 g / L, zinc sulfate is 30 g / L, sodium sulfate is 240 g / L, and the reaction temperature is 45°C.

[0135] Comparative Example 1

[0136] Select the representative example 1, remove S2 and S3, and directly mix the same amount of carbon quantum dots / TiO 2 The particles were made into a dispersion and added into a cellulose spinning solution. The rest was the same as in Example 1, which is used as Comparative Example 1.

[0137] Comparative Example 2

[0138] Select the representative example 1, remove S2 and S3, and directly mix the same amount of carbon quantum dots / TiO 2 The particles and polyvinyl pyrrolidone are prepared into a dispersion and added into a cellulose spinning solution, with polyvinyl pyrrolidone serving as a dispersant. The rest is the same as in Example 1, as Comparative Example 2.

[0139] The properties of the fibers prepared in the examples and comparative examples were tested, as shown in Table 1.

[0140] Table 1

[0141]

[0142] Note: Formaldehyde removal rate is the test data under visible light irradiation for 3 hours.

[0143] From Table 1 and Figure 1 It can be seen that both the embodiment and the comparative example have the effect of removing formaldehyde by visible light, but the test results of the embodiment are obviously better than those of the comparative example, and the formaldehyde removal effect of more than 90% can be achieved under visible light irradiation for 3 hours. In addition, the fiber performance prepared by comparative examples 1 and 2 shows a downward trend compared with that of the embodiment, among which the decline of comparative example 1 is greater, indicating that the carbon quantum dot / TiO 2The dispersion performance of the particles is poor. Comparative Example 2 uses polyvinyl pyrrolidone as a dispersant, which improves the carbon quantum dots / TiO 2 The dispersion of particles, but there are still some carbon quantum dots / TiO 2 The particles are in a state of agglomeration, and the dispersion effect is far less stable than the copolymerization and cross-linking of the embodiment. 2 The dispersion of particles directly determines the performance of the fiber, so the performance of Comparative Example 2 is better than that of Comparative Example 1, but the performance is still relatively poor compared with the examples.

[0144] The copolymerization and cross-linking method was used to modify the carbon quantum dots / TiO 2 The surface of the particles is cross-linked with polyvinyl pyrrolidone to modify the carbon quantum dots / TiO 2 The particles are coated to increase the carbon quantum dots / TiO 2 The purpose of particle dispersibility and compatibility with cellulose macromolecules is to avoid carbon quantum dots / TiO 2 The particles agglomerate; and the composite carbon quantum dots / TiO 2 The cross-linked polyvinyl pyrrolidone on the surface of the photocatalyst contains N-heterocycles and carbonyl groups. Under the acidic conditions of the coagulation bath, the cross-linked polyvinyl pyrrolidone is protonated to form hydrogen bonds with the hydroxyl groups on the cellulose macromolecules, further improving the strength of the fiber.

[0145] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.

[0146] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing antibacterial and formaldehyde-removing regenerated cellulose fiber, characterized in that: The preparation method comprises the preparation, modification, copolymerization and cross-linking of carbon quantum dots / TiO2 particles, the preparation of composite carbon quantum dots / TiO2 photocatalyst dispersion liquid, the preparation of blended spinning solution and spinning molding.

2. The method for preparing a bacteriostatic and formaldehyde-removing regenerated cellulose fiber according to claim 1, characterized in that: The carbon quantum dot / TiO2 particles are prepared by adding a titanate coupling agent and TiO2 into deionized water, stirring and mixing to obtain a mixed system; adding the mixed system into a JFS-550 type dispersing sand mill for grinding and dispersion, adding a carbon quantum dot solution to the mixed system after grinding, stirring and mixing for 30 to 60 minutes, so that the carbon quantum dots can be uniformly and stably attached to the surface of TiO2 treated with the coupling agent, and obtaining the carbon quantum dot / TiO2 particles after centrifugation, washing, filtering and drying.

3. The method for preparing a bacteriostatic and formaldehyde-removing regenerated cellulose fiber according to claim 2, characterized in that: The particle size of the carbon quantum dots is 20-50 nm, and the particle size of the TiO2 is 100-200 nm; the grinding and dispersion time is 60-90 min, and the rotation speed is 1500-2000 r / min; The mass ratio of the titanate coupling agent, TiO2 and deionized water is 5-8:15-20:90-100; The concentration of the carbon quantum dot solution is 10-20wt%; the carbon quantum dots in the carbon quantum dot solution account for 1-2% of the mass of TiO2.

4. The method for preparing a bacteriostatic and formaldehyde-removing regenerated cellulose fiber according to claim 1, characterized in that: The modification is as follows: adding carbon quantum dots / TiO2 particles into anhydrous ethanol, then adding γ-methacryloxypropyltrimethoxysilane, stirring for 20 to 30 minutes, adjusting the pH to 4.5 to 6, heating to 40 to 50° C. and reacting for 90 to 120 minutes, modifying the unsaturated double bonds on the surface of the carbon quantum dots / TiO2 particles, and obtaining the modified carbon quantum dots / TiO2 particles after centrifugation, washing, filtering and drying after the reaction.

5. The method for preparing a bacteriostatic and formaldehyde-removing regenerated cellulose fiber according to claim 4, characterized in that: The added amount of the γ-methacryloxypropyltrimethoxysilane is 18-22% of the mass of the carbon quantum dots / TiO2 particles.

6. The method for preparing a bacteriostatic and formaldehyde-removing regenerated cellulose fiber according to claim 1, characterized in that: The copolymerization and cross-linking process comprises the following steps: adding the modified carbon quantum dots / TiO2 particles into anhydrous ethanol and stirring for 20 to 30 minutes, then adding N-vinyl pyrrolidone, an initiator, and a cross-linking agent and continuing to stir for 10 to 20 minutes, heating to 60 to 70° C. and performing copolymerization and cross-linking reaction for 4 to 6 hours, generating cross-linked polyvinyl pyrrolidone on the surface of the modified carbon quantum dots / TiO2 particles to coat the modified carbon quantum dots / TiO2 particles, and obtaining a composite carbon quantum dots / TiO2 photocatalyst after centrifugation, washing, filtering, and drying after the reaction is completed.

7. The method for preparing a bacteriostatic and formaldehyde-removing regenerated cellulose fiber according to claim 1, characterized in that: The amount of N-vinyl pyrrolidone added is 32-40% of the mass of the modified carbon quantum dots / TiO2 particles; The amount of the initiator added is 0.5-1.5% of the mass of N-vinyl pyrrolidone, and the amount of the cross-linking agent added is 2-4% of the mass of N-vinyl pyrrolidone; The initiator is azobisisobutyronitrile, and the crosslinking agent is N,N , -Methylenebisacrylamide.

8. The method for preparing a bacteriostatic and formaldehyde-removing regenerated cellulose fiber according to claim 1, characterized in that: The composite carbon quantum dot / TiO2 photocatalyst dispersion is prepared by adding the composite carbon quantum dot / TiO2 photocatalyst into deionized water and stirring for 10 to 20 minutes to obtain the composite carbon quantum dot / TiO2 photocatalyst dispersion; The mass ratio of the composite carbon quantum dots / TiO2 photocatalyst to deionized water is 1:8-10.

9. The method for preparing a bacteriostatic and formaldehyde-removing regenerated cellulose fiber according to claim 1, characterized in that: The preparation of the blended spinning solution is as follows: using cellulose pulp as a raw material, and preparing a cellulose spinning solution through the processes of impregnation, pressing, crushing, aging, yellowing, dissolving, filtering, degassing, etc.; adding the composite carbon quantum dot / TiO2 photocatalyst dispersion in proportion in the dissolving process or adding it by injection before spinning and mixing them evenly to prepare a blended spinning solution; The composite carbon quantum dots / TiO2 photocatalyst in the composite carbon quantum dots / TiO2 photocatalyst dispersion is 0.2-1.0wt% of the cellulose content in the cellulose spinning solution.

10. The method for preparing the antibacterial and formaldehyde-removing regenerated cellulose fiber according to claim 1, characterized in that: The spinning forming is that the blended spinning solution is ejected from the spinneret and then formed in a coagulation bath to obtain a primary fiber bundle, and then subjected to inter-disk drawing, two-bath drawing, post-treatment and other processes to obtain the antibacterial and formaldehyde-removing regenerated cellulose fiber prepared by the present invention; In the coagulation bath, sulfuric acid is 100-150 g / L, zinc sulfate is 30-50 g / L, sodium sulfate is 210-240 g / L, and the reaction temperature is 40-45°C.

Citation Information

Cited By

  • Antibacterial activated carbon-silver ion composite photocatalyst and preparation method thereof

    CN121571177A